Nerve Growth Factor Stimulates Multisite Tyrosine Phosphorylation and Activation of the Atypical Protein Kinase C's via a src Kinase Pathway - Wooten, Marie W. (American Society for Microbiology, 2001)
Atypical protein kinase C (PKC) isoforms are required for nerve growth factor (NGF)-initiated differentiation of PC12 cells. In the present study, we report that PKC-ι becomes tyrosine phosphorylated in the membrane coincident with activation posttreatment with nerve growth factor. Tyrosine phosphorylation and activation of PKC-ι were inhibited in a dose-dependent manner by both PP2 and K252a, src and TrkA kinase inhibitors. Purified src was observed to phosphorylate and activate PKC-ι in vitro. In PC12 cells deficient in src kinase activity, both NGF-induced tyrosine phosphorylation and activation of PKC-ι were also diminished. Furthermore, we demonstrate activation of src by NGF along with formation of a signal complex including the TrkA receptor, src, and PKC-ι. Recruitment of PKC-ι into the complex was dependent on the tyrosine phosphorylation state of PKC-ι. The association of src and PKC-ι was constitutive but was enhanced by NGF treatment, with the src homology 3 domain interacting with a PXXP sequence within the regulatory domain of PKC-ι (amino acids 98 to 114). Altogether, these findings support a role for src in regulation of PKC-ι. Tyrosine 256, 271, and 325 were identified as major sites phosphorylated by src in the catalytic domain. Y256F and Y271F mutations did not alter src-induced activation of PKC-ι, whereas the Y325F mutation significantly reduced src-induced activation of PKC-ι. The functional relevance of these mutations was tested by determining the ability of each mutant to support TRAF6 activation of NF-κB, with significant impairment by the Y325F PKC-ι mutant. Moreover, when the Y352F mutant was expressed in PC12 cells, NGF's ability to promote survival in serum-free media was reduced. In summary, we have identified a novel mechanism for NGF-induced activation of atypical PKC involving tyrosine phosphorylation by c-Src.